Effects of Daidzin and analogue of Ganoderma sinense on bacterially-expressed human hexokinase isoform 2 for anti-dengue drug design - Asman, Nur Atikah; Tanbin, Suriyea; Ahmad Fuad, Fazia Adyani (IIUM Press, 2020)
Dengue disease, which is caused by dengue virus (DENV) has been a major worldwide concern, with increased number of cases each year. Currently, there are no specific medications to treat the disease. Hence, there is a dire need to develop novel drugs for disease treatment. Glycolysis is a metabolic pathway that serves as the main source of energy for DENV replication and targeting the pathway is one of the ideal approach to discover new anti-DENV drugs. This paper focuses on the inhibition of the human hexokinase isoform 2 (HK2) enzyme, which is one of the important enzymes in glycolysis, in the quest to disrupt DENV replication. In order to search for potential inhibitors, two methods were conducted, which are ligand-based screening and structure-based screening approaches. The docking of Daidzin, which was derived from Kudzu, a Japanese plant, has shown the nearest binding affinity score (-7.94 kcal/mol) to Glucose‘s (GLC), which is -8.15 kcal/mol. Meanwhile, from the ligand-based screening, Ethyl (2R)-2-[[3-[2-[(4-methylbenzoyl)amino]ethyl]-[1,2,4]triazolo[4,3-b]pyridazin-6-yl]sulfanyl]butanoate, a compound which is the analogue of Ganoderma sinense with a binding score of -8.43 kcal/mol was chosen for the subsequent inhibition studies. These compounds were further analysed in an inhibition assay to determine the effects of of the potential naturally-derived inhibitors on the activity of HK2. The outcome from the inhibition study shows that both compounds exhibited substantial inhibition on HK2 enzyme, where Daidzin, at 0.5 mM, resulted in HK2 remaining activity of 88.98%, while Ethyl (2R)-2-[[3-[2-[(4-methylbenzoyl)amino]ethyl]-[1,2,4]triazolo[4,3-b]pyridazin-6-yl]sulfanyl]butanoate (Ethyl (2R)) resulted in 69.58% of HK2 remaining activity, also at 0.5 mM concentration. In conclusion, this study has served as a platform for the development of anti-dengue drugs based on naturally-derived compounds, which is anticipated to be a safer option for dengue treatment